Hybridising Teaching Personal Social Responsibility (TPSR) and Problem Based Learning (PBL) in Physical Education - Nur Indri Rahayu; Adang Suherman; Bambang Abdul Jabar (Universitas Pendidikan Indonesia, 2018)
The aim of this research was to test the effectiveness of TPSR and PBL in physical education to increase student’s personal and social responsibility. This is quasi experimental research with pretest posttest control group design, Sample of this research were senior high school as many as 122 student’s. The instrument used was an adaptation of Tool for Assessing Responsibility-Based Education (TARE) Observation, while the data analysis using paired sample t-test and independent sample t-test. The results showed there was significant effect of hybridizing TPSR and PBL in enhancing student’s personal and social responsibility. Hybridizing TPSR and PBL is effective to increase student’s personal and social responsibility in physical education. Next, more in-depth research is required by involving a random sampling with larger sample size or by using another scientific learning approach such as inquiry or project based learning.AbstrakPenelitian ini bertujuan untuk menguji efektivitas hibridasi program TPSR dan PBL dalam pendidikan jasmani untuk meningkatkan tanggung jawab personal dan sosial siswa. Penelitian ini menggunakan quasi eksperimental dengan desain pretest posttest control group, Sampel penelitian ini adalah siswa SMA sebanyak 122 orang. Instrumen yang digunakan adalah adaptasi Tool for Assessing Responsibility Based Education (TARE), sedangkan analisis data menggunakan paired sample t-test dan independent sample t-test. Hasil penelitian menunjukkan ada pengaruh yang signifikan dari hibridisasi TPSR dan PBL dalam meningkatkan tanggung jawab personal dan sosial siswa. Hibridisasi TPSR dan PBL dalam pendidikan jasmnai efektif untuk meningkatkan tanggung jawab personal dan sosial siswa. Diperlukan penelitian yang lebih mendalam dengan melibatkan sampling acak dan ukuran sampel yang lebih besar atau dengan menggunakan pendekatan pembelajaran ilmiah lain seperti inquiry learning atau project based learning